IMPACT OF BUSINESS LEARNING AND SOCIAL MEDIA PROBLEMS ON BUSINEER INTERESTS IN STUDENTS OF THE UNIVERSITY OF MAKASSAR - Imam Ahmad Syadiq; Agus Syam, Asmayanti, Muhammad Rakib, Muhammad Jufri (BORJUIS: JURNAL OF ECONOMY, 2025)
The objective of this study is (1) to demonstrate that there is a significant influence of entrepreneurship learning on entrepreneurial interests of students of the Makassar State University Programme of Entrepreneurships Studies. (2) To demonstrate the significant impact of the use of social media on the entrepreneur interest of Students of the University of Makassar Programme. (3) To prove that there are significant influences of entreprenorship learning and social media utilization on enterprise interests. This research method uses quantitative methods and instruments used in the form of angles. The population in this study amounted to 378 students of the entrepreneurship study program of Makassar State University, taking a sample of 193 students from the total population. The data analysis used in this study uses double linear regression analysis. The results of this study show that: (1) There was a significant positive influence of entrepreneurship learning on entrepreneurial interest in students of Makassar State University's entrepreneurhood study program with a regression coefficient of 0.261. (2) There was an significant positive impact of social media use on enterprise interests of students of the Makassar state University's enterprise study programme with the regression factor of 0.375.